A 71-nucleotide deletion in the periaxin gene in a Romani patient with early-onset slowly progressive demyelinating CMT - Baránková, L; Sisková, D; Hühne, K; Vyhnálková, E; Sakmaryová, I; Bojar, M; Rautenstrauss, B; Seeman, P (European journal of neurology, 2008)
BACKGROUND: Mutations in the periaxin (PRX) gene cause autosomal recessive demyelinating neuropathy Charcot-Marie-Tooth (CMT) type 4F. To date, 10 non-sense or frameshift PRX mutations have been reported in patients with early-onset neuropathy and further disease course consistent with either Dejerine-Sottas neuropathy or slow-progressive demyelinating CMT. METHODS: We sequenced 59 patients from 55 Czech families including four unrelated patients of Romani (Gypsy) origin with early-onset CMT displaying decreased nerve conduction velocities. RESULTS: We identified a novel homozygous mutation c.3286_3356del71 (K1095fsX18) in one Romani patient showing very slow disease progression. Amongst non-Romani Czech CMT patients, PRX mutations have been proven to be very rare.
Keywords: genetické testování; membránové proteiny; Membrane Proteins; kojenec; věk při počátku nemoci; mužské pohlaví; rodokmen; Pedigree; Charcotova-Marieova-Toothova nemoc; Infant; Charcot-Marie-Tooth Disease; Demyelinating Diseases; Sequence Deletion; Romové; sekvenční delece; Base Sequence; sekvence nukleotidů; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; demyelinizační nemoci; Age of Onset; Roma; Genetic Testing; Female; lidé; Male